2010
DOI: 10.1371/journal.pone.0010326
|View full text |Cite
|
Sign up to set email alerts
|

Epigenetic Variation in Mangrove Plants Occurring in Contrasting Natural Environment

Abstract: BackgroundEpigenetic modifications, such as cytosine methylation, are inherited in plant species and may occur in response to biotic or abiotic stress, affecting gene expression without changing genome sequence. Laguncularia racemosa, a mangrove species, occurs in naturally contrasting habitats where it is subjected daily to salinity and nutrient variations leading to morphological differences. This work aims at unraveling how CpG-methylation variation is distributed among individuals from two nearby habitats,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

25
277
1
4

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 322 publications
(317 citation statements)
references
References 55 publications
25
277
1
4
Order By: Relevance
“…While the structure of B1 and B2 can only be shaped through natural selection, B3 could be direct changed by the environment. The epigenetic differentiation was observed in contrast habitats without variation differentiation (Foust et al., 2016; Gugger et al., 2016; Lira‐Medeiros et al., 2010; Schulz et al., 2014), but it remained unexplored how stable and inheritable the B3 variation is in these studies. Common garden filtered the plastic B3 variation in our study, and epigenetic divergence between populations in the introduced region and in its original region was weakened.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the structure of B1 and B2 can only be shaped through natural selection, B3 could be direct changed by the environment. The epigenetic differentiation was observed in contrast habitats without variation differentiation (Foust et al., 2016; Gugger et al., 2016; Lira‐Medeiros et al., 2010; Schulz et al., 2014), but it remained unexplored how stable and inheritable the B3 variation is in these studies. Common garden filtered the plastic B3 variation in our study, and epigenetic divergence between populations in the introduced region and in its original region was weakened.…”
Section: Discussionmentioning
confidence: 99%
“…Epigenetic diversity can generate massive heritable variation of ecologically relevant plant traits such as root allocation, drought tolerance and nutrient plasticity (Zhang, Fischer, Colot, & Bossdorf, 2013), and it appears to increase the productivity and stability of plant populations in Arabidopsis thaliana under artificial conditions (Latzel et al., 2013). An increasing number of studies have also demonstrated the common existence and significant role of epigenetic variation in plant populations of herbs (Foust et al., 2016; Herrera, Medrano, & Bazaga, 2014; Medrano et al., 2014; Preite et al., 2015; Schulz, Eckstein, & Durka, 2014), shrubs (Avramidou, Ganopoulos, Doulis, Tsaftaris, & Aravanopoulos, 2015; Herrera & Bazaga, 2013, 2016), and trees (Guarino, Cicatelli, Brundu, Heinze, & Castiglione, 2015; Gugger, Fitz‐Gibbon, PellEgrini, & Sork, 2016; Lira‐Medeiros et al., 2010; Platt, Gugger, Pellegrini, & Sork, 2015; Sáez‐Laguna et al., 2014) under natural conditions. Therefore, epigenetic variation can be a very important mechanism for invasive plant success in a broad range of environments (Douhovnikoff & Dodd, 2014; Richards, Schrey, & Pigliucci, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…However, because such unique epialleles that cause phenotypic changes can only be distinguished from genetic variants by in-depth molecular analyses, epigenetic alterations independent of observable phenotypes are now being analyzed at the genomewide level. Several studies in nonmodel organisms have shown by methylation-sensitive amplified polymorphism (MSAP) analyses that natural populations vary more in DNA methylation than in DNA sequence, that is, their epigenetic diversity is higher than their genetic diversity (Cervera et al 2002;Keyte et al 2006;Salmon et al 2008;Herrera and Bazaga 2010;Lira-Medeiros et al 2010). In addition, DNA methylation patterns were analyzed in Arabidopsis using high-throughput sequencing of bisulfite-treated genomic DNA (BS-Seq).…”
Section: The Molecular Basis Of Epigenetic Variationmentioning
confidence: 99%
“…Broadening the search for naturally occurring epialleles revealed variation in DNA methylation patterns in several nonmodel species living in diverse natural settings (Salmon et al 2008;Marfil et al 2009;Herrera and Bazaga 2010;Lira-Medeiros et al 2010;Paun et al 2010). In these reports, cytosine methylation polymorphisms were detected using MSAP analyses that enables the sampling of information about the methylation status across the genome without prior knowledge of the genome sequence.…”
Section: Epigenetic Variation In Natural Populationsmentioning
confidence: 99%
See 1 more Smart Citation